Rheumatological disorder (RD) in Indian women above 40 years of age: A cross-sectional WHO-ILAR-COPCORD-based survey - Susheel Kudial; Vishal R Tandon; Annil Mahajan (Journal of Mid-Life Health, 2015)
Aim and Objective: To evaluate rheumatological profile among Indian women above 40 years. Materials and Methods: A cross-sectional survey was carried out for a period of one year using pre-validated questionnaire of COPCORD /WHO-ILAR. Those who complain of pain, tenderness, stiffness or swelling were subjected to clinical evaluation and diagnosis was established using the ACR′s criteria for various RDs. Results: Mean age of the patients was 55.06 ± 6.82 years, mean age at menopause was 47.30 ± 2.50 years and the mean time since menopause was 9.077 ± 5.43 years. Among the total population evaluated (N = 130), 37.69% women presented with RD and 37.06% women among the menopausal women had RD with the most common being low backache (16.92%), followed by osteoarthritis (12.30%), fibromyalgia (3.84%) and rheumatoid arthritis (2.30%). The most common site involved was knee (9.23%) followed by lumbar spine (8.46%), hip (3.07%) and other sites (16.92%) such as neck, upper back, hand joints, shoulder, thighs, etc. Study failed to show any statistical correlation with any socio-demographic or other parameters of interest with RD. HAQ-DI (Health Assessment Questionnaire Disability Index) was found to be highly significant (P < 0.000) in 13.84% women when correlated with RD. Conclusion: The prevalence of RD is substantially high among Indian women above 40 years demanding attention of health care providers.